Implementation of Sustainable Management-Based Design Thinking to Reduce Flower Board Waste in Higher Education - Sabrinadiza Balya; Elina Sabella Ambari; Annisa Rachmah; Asep Taryana (Journal of Educational Management Research, 2025)
Universities pursuing Green University status often face a critical conflict between sustainability mandates and the deep-seated cultural tradition of receiving floral boards (papan bunga), which generates massive, unmanageable waste. This study applies the Design Thinking methodology to resolve this cultural-environmental conflict at a state university in South Tangerang. Through the Empathize and Define stages, the study identified that the root problem lay not in waste management, but in the cultural habit of sending physical tokens. Consequently, the Ideate phase formulated a "Dual-Strategy Approach": a Primary Prototype (Official Appeal for Substitution) to eliminate the waste source, and a Secondary Prototype (Standardized Handling SOP) as a contingency for waste management. Field testing of the Primary Prototype during the Rector's Inauguration achieved a 100% reduction in waste, reducing floral board deliveries from over 300 to zero, substituting 317 tree seedlings and digital greetings. Given this absolute success in prevention, the Secondary Prototype (SOP) was not operationally executed but was validated as a necessary blueprint for future compliance risks. While the intervention effectively eliminated the waste source, the high volume of substituted seedlings introduced a new logistical challenge regarding land allocation. The study concludes that shifting the operational focus from downstream handling to upstream prevention via formal policy nudging is the most effective strategy for achieving genuine zero-waste targets in academic institutions.